Intending to deceive versus deceiving intentionally in indifferent lies. (3rd July 2020) - Wiegmann, Alex; Rutschmann, Ronja
ABSTRACT: Indifferent lies have been proposed as a counterexample to the claim that lying requires an intention to deceive. In indifferent lies, the speaker says something she believes to be false (in a truth-warranting context) but does not really care about whether the addressee believes what she says. Krstić (2019) argues that in such cases, the speaker deceives the addressee intentionally and, therefore, indifferent lies do not show that lying does not require an intention to deceive. While we agree that the speaker deceives the addressee intentionally, we resist Krstić's conclusion by pointing out that there is a difference between deceiving intentionally and intending to deceive. To this aim, we presented 268 participants with a new variant of an indifferent lie and asked whether the speaker lied, whether she had an intention to deceive, and whether she deceived intentionally. Whereas the majority of participants considered the speaker to have deceived the addressee intentionally, most denied that the speaker had an intention to deceive the addressee. Hence, indifferent lies still challenge widely accepted definitions of lying.